El efecto tabla redonda comunicación y política pública - Jaramillo López, Juan Camilo (2024)
The construction of public policy, in addition to political action, is communicative action. As a mechanism that complies with and gives dynamism to the principle of publicity and as an exercise in public communication that admits agreements, consensuses and commitments, it organizes and gives character to citizen participation. The “round table” effect uses metaphor to refer to the kind of broad, horizontal and inclusive conversation that this democratic exercise requires, both in public deliberation and in direct spaces of participation.